The Emotional Impact of Sports Sponsorships: A Sentiment Analysis of Public Reactions on Reddit - Özer, Şevket Cihat; Ulusay, Nurten; Gözen, İlhan and Keskin, Muzaffer Toprak (International Review of Management and Marketing, 2025)
This article discusses the role of sports sponsorships and the impact of sponsorship agreements on various stakeholders, along with the emotional reactions they evoke in the public. Sponsorship is viewed as a strategic partnership between companies and sports organizations, with the primary goal of increasing brand visibility and ensuring financial growth. The sentiment analyses presented in the article reveal a complex interaction between sponsorships and public opinion, examining the influence of emotions such as anger, anticipation, disgust, fear, joy, sadness, surprise and trust. These emotions are significantly affected by factors such as the commercialization of sports, manipulative practices in sponsorship agreements and ethical concerns. In this respect, the study approaches the phenomenon of sports sponsorship from a sports economics perspective, drawing attention to the balance between economic interests and societal values. The study emphasizes that while sponsorships can enhance sports experiences, they can lead to negative perceptions if financial interests overshadow the values and integrity of sports. The article highlights the importance of transparency and ethical practices in sponsorship agreements and suggests that future research should delve deeper into the emotional effects of sponsorships. Additionally, it stresses the need for research that extends beyond platforms like Reddit to include other social media channels.